2019
DOI: 10.5152/iao.2019.6492
|View full text |Cite
|
Sign up to set email alerts
|

Extra-Cochlear Insertion in Cochlear Implantation: A Potentially Disastrous Condition

Abstract: The Journal of International Advanced Otology (J Int Adv Otol) is an international, peer reviewed, open access publication that is fully sponsored and owned by the European Academy of Otology and Neurotology and the Politzer Society. The journal is published triannually in April, August, and December and its publication language is English. The scope of the Journal is limited with otology, neurotology, audiology (excluding linguistics) and skull base medicine. The Journal of International Advanced Otology aims… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…Proper visualization is crucial to confirming accurate electrode placement, obtaining adequate exposure is of immense importance for the surgeon. This is supported by previous studies that have found identification of anatomic landmarks to be of extreme value, even when visualization is made difficult by unexpected factors, such as mucosal edema, fibrosis, ossification, facial nerve dehiscence, or other abnormalities (3,4,6,8,9,11,13,14).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Proper visualization is crucial to confirming accurate electrode placement, obtaining adequate exposure is of immense importance for the surgeon. This is supported by previous studies that have found identification of anatomic landmarks to be of extreme value, even when visualization is made difficult by unexpected factors, such as mucosal edema, fibrosis, ossification, facial nerve dehiscence, or other abnormalities (3,4,6,8,9,11,13,14).…”
Section: Discussionsupporting
confidence: 72%
“…Difficulties with anatomic visualization have often been noted in cases of CI misplacement. In this series, the most cited technical factor was poor visualization or misidentification of the round window (3,6,8,9,11,13,14). Thus, lack of visualization of the round window may be associated with CI misplacement.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…According to a literature review, most studies regarded the following situations as reimplantation: (1) removal of the initial electrodes for various reasons and implantation of a new device on the ipsilateral or contralateral side, which was the most common scenario defined as reimplantation ( Lassig et al, 2005 ); (2) replacement of the failed hybrid CI with short electroacoustic stimulation (EAS) electrodes or full-length electrodes ( Kamat et al, 2011 ; Jayawardena et al, 2012 ; Dunn et al, 2015 ); (3) reinsertion of the initial electrodes into the cochlea in cases of device migration ( Luo et al, 2020 ); (4) reinsertion of the initial electrodes into the cochlea on the operation day or within a few days of the operation due to the electrodes in incorrect insertion places, such as the internal auditory canal, eustachian tube, vestibul. ( Gözen et al, 2019 ); and (5) simultaneous implantation on both sides when patients with unilateral CI accept reimplantation surgery ( Tang et al, 2019 ).…”
Section: Part Ii: Current Deficiencies and Future Research Directionsmentioning
confidence: 99%
“…Extracochlear electrode array placements like placement in the canal of the internal carotid artery or the Eustachian tube have been very rarely reported in the literature [ 49 , 72 ].…”
Section: Post-operative Imagingmentioning
confidence: 99%